Papuan Indigenous Women in a Patriarchal Culture: A Qualitative Study - Uswatun Khasanah; Bresca Merina (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study aims to explore the position and role of Indigenous Papuan women (OAP) in the context of patriarchal culture in Sebyar Rejosari Village, Tomu District, Teluk Bintuni Regency, West Papua. The research employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews with ten informants (married and unmarried women), and documentation. The results of the study indicate that patriarchal culture significantly disadvantages women, as evidenced by their limited access to education and healthcare, both physical and mental. These limitations lead to stress and feelings of low self-esteem among OAP women. The author hopes for a shift through empowering women via higher education and equal access to resources. This research supports postcolonial feminist theory, which emphasizes the need for the decolonization of gender thinking. The best solution is to integrate local values with empowerment programs to improve the position of women in society. Independent and well-educated women are expected to contribute significantly to the development of their communities.